Design of Lampung Bay Waterfront Using Poetic Architecture Approach - Shofia Islamia Ishar; Muhammad Syahroni (International Conference on Engineering and Technology Development (ICETD), 2014)
Lampung Bay is one of the precious natural elements in Bandar Lampung. The character, the wealth of seafood, and the beauty of the landscape are a good potency that can be synergies to the city life. Preservation and beauty of Lampung Bay may improve the environmental quality of the city so that the need to maintain its existence becomes very urgent.Unfortunately the existence of Lampung Bay has not been appreciated as a valuable natural asset. It conditions is neglected and overflowing trash. The perception that the water area as a“behind" area or effluent areais prevail so it needs deliberate action to change this perception by doing a waterfront oriented design in Lampung Bay.Waterfront oriented design in Lampung Bay also requires an appropriate approach in order to create sustainability to preserve the nature. Poetic Architectureis selected as the most appropriate approach because it can cause a sense of love to the nature by displaying the grandeur of the nature through architecture and activities that can grant appreciation to the nature..